2020
DOI: 10.3390/ijerph17228528
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Quality of Life and Sociodemographic, Physical and Mental Health Variables in People over 65 in the Community of Madrid

Abstract: Except in the case of depression, there are few studies that analyze mental health variables related to quality of life (QoL) in people over 65 years of age. The objective of this study is to analyze the relationship between QoL and the following variables: sociodemographic and physical and mental health of people over 65 years of age. The sample was randomly selected and consists of men and women between 65 and 84 years of age (N = 555) from the Community of Madrid. Mental disorders were evaluated with the CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
5
1
1
Order By: Relevance
“…Within families, women tend to bear a greater share of the burden of care, as they are accustomed to care-giving ( Minello et al., 2021 ), as women have historically provided on average 3.3 times more care than men in the household ( Addati et al., 2018 ). According to some studies this caregiving overload may be related to the increased prevalence of mental disorders in women ( Ausín et al., 2020b ; González-de Paz et al., 2016 ; Zygouri et al., 2021 ). Additionally, different systematic reviews have reported a consistent relationship between being a victim of domestic violence and abuse and having mental disorders across the diagnostic spectrum, as well as sexual and other types of violence have also shown consistent relationships with the presence of depression, anxiety and post-traumatic stress ( Oram et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within families, women tend to bear a greater share of the burden of care, as they are accustomed to care-giving ( Minello et al., 2021 ), as women have historically provided on average 3.3 times more care than men in the household ( Addati et al., 2018 ). According to some studies this caregiving overload may be related to the increased prevalence of mental disorders in women ( Ausín et al., 2020b ; González-de Paz et al., 2016 ; Zygouri et al., 2021 ). Additionally, different systematic reviews have reported a consistent relationship between being a victim of domestic violence and abuse and having mental disorders across the diagnostic spectrum, as well as sexual and other types of violence have also shown consistent relationships with the presence of depression, anxiety and post-traumatic stress ( Oram et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different systematic reviews have reported a consistent relationship between being a victim of domestic violence and abuse and having mental disorders across the diagnostic spectrum, as well as sexual and other types of violence have also shown consistent relationships with the presence of depression, anxiety and post-traumatic stress ( Oram et al., 2017 ). On the other hand, the consequences of mental health problems are not only limited to the clinical or health domain, with several studies showing that all aspects of quality of life are vulnerable to mental health conditions ( Ausín et al., 2020b ; Martínez-Alonso et al., 2007 ; Nouri et al., 2021 ; Sivertsen et al., 2015 ). A recent Spanish study ( AVIFES, 2018 ), shows important differences in the quality of life outcomes of women with mental health problems compared to other women (with and without disabilities), as well as to men with mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…With evidence of increasing rates of mental illness ( Calling et al, 2017 ; Patalay and Gage, 2019 ), there is growing concern over the personal and socioeconomic impact of psychological distress ( McDaid et al, 2019 ; Ausín et al, 2020 ). A key factor in alleviating the undesirable outcomes associated with mental illness is early therapeutic intervention ( Cook et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the presence of mental health problems and QoL has been extensively studied in the field of severe mental disorders. There is little research on the relationship between mental health and QoL in the general population [ 17 , 18 , 19 ] and even less in the migrant population [ 9 ]. Despite this, it is likely that, in this population, QoL as an indicator of well-being is negatively affected by the presence of mental health problems, a relationship that has been found in other closely related indicators such as subjective well-being [ 20 ], psychological well-being, and life satisfaction [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%